2017
DOI: 10.1007/s10532-017-9789-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of biogenic substrates on sulfamethoxazole biodegradation kinetics by Achromobacter denitrificans strain PR1

Abstract: Pure cultures have been found to degrade pharmaceutical compounds. However, these cultures are rarely characterized kinetically at environmentally relevant concentrations. This study investigated the kinetics of sulfamethoxazole (SMX) degradation by Achromobacter denitrificans strain PR1 at a wide range of concentrations, from ng/L to mg/L, to assess the feasibility of using it for bioaugmentation purposes. Complete removal of SMX occurred for all concentrations tested, i.e., 150 mg/L, 500 µg/L, 20 µg/L, and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 63 publications
3
27
0
Order By: Relevance
“…The successful colonization of a bioreactor by inoculated bacteria is challenging as they are likely to encounter the following obstacles within the biological unit, i.e., environmental pressure due to protozoan grazing and/or competition with indigenous microorganisms as well as fluctuations of the abiotic factors such as temperature, pH, salinity, the hydrodynamic conditions, organic loading rate, and the availability of nutrients and oxygen, which causes them to die or to wash out of the system along with the effluent [23][24][25][26]. A versatile degradation capacity towards a variety of compounds is often reported as being a pivotal competence of potential candidates for bioaugmentation [27,28]. However, adding bacteria with the desirable catabolic capabilities into the AS does not always guarantee an enhanced biodegradation of the compounds in wastewater [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The successful colonization of a bioreactor by inoculated bacteria is challenging as they are likely to encounter the following obstacles within the biological unit, i.e., environmental pressure due to protozoan grazing and/or competition with indigenous microorganisms as well as fluctuations of the abiotic factors such as temperature, pH, salinity, the hydrodynamic conditions, organic loading rate, and the availability of nutrients and oxygen, which causes them to die or to wash out of the system along with the effluent [23][24][25][26]. A versatile degradation capacity towards a variety of compounds is often reported as being a pivotal competence of potential candidates for bioaugmentation [27,28]. However, adding bacteria with the desirable catabolic capabilities into the AS does not always guarantee an enhanced biodegradation of the compounds in wastewater [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that the presence of a biogenic substrate, e.g. acetate or succinate, provided for an 8-fold increase of SMX biotransformation kinetics by PR1 [14]. In the current study, the initial concentration of acetate was approximately 137 to 152 mg COD L -1 , supplemented with preclarified wastewater to (i) the bioaugmented reactor (A4) (Fig.…”
Section: Effect Of Acetate Addition On the Biotransformation Of Smxmentioning
confidence: 53%
“…Pure culture biotransformation tests had previously shown that the A.denitrificans PR1 is capable of biotransformation of SMX under both aerobic [14] and anoxic conditions (data not shown). Hence the extent of SMX removal under anoxic conditions was also assessed and compared to those obtained in aerobic conditions.…”
Section: Anoxic Experiementsmentioning
confidence: 90%
See 2 more Smart Citations